Effect of bonded stepped and scarf repair on impact damaged glass fibre reinforced polymer composite properties. (28th July 2021) - Mithun, H.A.; Krishna, M.; Shrikanth, B.
The objective of the present work is to investigate the effect of bonded stepped and scarf repair methods on the tensile strength restoration of glass fibre epoxy composites. The composites were fabricated using hand lay-up technique and the specimens were subjected to impact at two different energies of 41 J and 44.3 J. The damage was assessed using dye penetration along with CAD image scaling technique. Damage repaired specimens were characterised for the tensile test which was carried out on a cut portion of the plate having repair identical to the parent laminate. Tensile strength restoration for 41 J and 44.3 J impact energies of scarf repaired laminates was 69.26% and 64.19%, respectively, whereas for step repaired laminates it was 63.46% and 59.74% respectively.